If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -28 = x + -2 Reorder the terms: -28 + 4x = x + -2 Reorder the terms: -28 + 4x = -2 + x Solving -28 + 4x = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -28 + 4x + -1x = -2 + x + -1x Combine like terms: 4x + -1x = 3x -28 + 3x = -2 + x + -1x Combine like terms: x + -1x = 0 -28 + 3x = -2 + 0 -28 + 3x = -2 Add '28' to each side of the equation. -28 + 28 + 3x = -2 + 28 Combine like terms: -28 + 28 = 0 0 + 3x = -2 + 28 3x = -2 + 28 Combine like terms: -2 + 28 = 26 3x = 26 Divide each side by '3'. x = 8.666666667 Simplifying x = 8.666666667
| 64=-10v+4 | | 4x-x+7x=9 | | 7x-8=5x+2x+10 | | 1.1x-0.4x-225000=0 | | 2x-3-9=-x | | 2-7y+5=4y+15-7y | | 5x+4(x-6)=12 | | 5(x-4)+2x=7x-1 | | 15-(x+6)=3x-7 | | 3+4x=5x-6 | | 4v+40=8(v+7) | | 3x-8x+6=7x-1 | | 10+10=(208)+10 | | 2n+6=-10 | | 3.25-y=-0.75 | | Z=4+7i | | 4x+(x-3)6=92 | | 3.25-y=0.75 | | F(x)=-x^2+3x-2 | | 12-(3m+3)=2+3m-11 | | 5A+2(3A-5)=1+5(A+2)-A+3(3-4) | | 6x+2x-4=3x-3+12 | | 4t+35=10t-37 | | 2b+4=-18+-9 | | 2y+x-3=0 | | 8m+4=8m | | (x-380)(x^2+2)=0 | | 2x+x+y=180 | | 4x+(4x-3)6=92 | | 2(x-5)=7x+6x | | x+30=4x+9 | | 10=60-5x |